13-19 Roxburgh Street, Kelso, 1983-4 (Scottish Historical and Archaeological Internet Reports, 2003)
A brief account of existing documentary evidence is presented. This is followed by a phased archaeological description. There are eight phases commencing in the later medieval period continuing into the early 20th century. This excavation has provided evidence that 13-19 Roxburgh Street was within the occupied area of the settlement of Easter Kelso from the 13th and 14th centuries, with evidence of wells, a possible building platform parallel to the modern street, and pits for both rubbish and quarrying. In addition the corn-drying kiln is indicative of an open yard area behind the street frontage during the 16th century, if not earlier. Such activity does not distinguish it as being urban or rural, since kilns have been encountered in both urban and rural locations. The infilling of the backlands of the building plots during the 18th and 19th centuries indicates the main period or urban expansion, but activity in the 17th century suggests that there may be continual occupation of the site from the medieval period onwards.